Pre-Foundation Investigation Using Electrical Resistivity Method: A Case Study of Proposed Phase II, Faculty of Law Building, Federal University Oye-Ekiti, Nigeria (Lafia Journal of Scientific and Industrial Research, 2024)
The proposed Phase II, Faculty of Law Building, was investigated to determine the competence of the sub-soil for building construction. The Electrical Resistivity method was employed for the geophysical investigation. The 2-D Electrical Resistivity Imaging (ERI) and Vertical Electrical Sounding (VES) techniques were adopted using the dipole-dipole electrode and Schlumberger arrays respectively. Using an electrode spacing (a) of 5 m and expansion factor (n) varying from 1 – 5, electrical resistivity measurements were taken along two traverses having South – North (SN) and East – West (EW) orientations respectively. Thirteen VES stations were occupied within the study area with half-current electrode spacing (AB/2) ranging from 1 – 65 m. The interpretation of the geophysical data was carried out using DIPRO software. The 2D ERI showed that the sub-soil along traverse 1 and northern part of traverse 2 has high resistivity values (>900 Ωm) at 4.5 m depth. The geoelctric sections identified three geologic layers comprising topsoil, weathered layer and fresh basement. The electrical resistivity results revealed that the sub-soils on or within the proposed site are found to be fairly competent for engineering structure.
Keywords: Engineering geophysics; VES; 2-D ERI; Geoelectric section